Prevalence and classification of equinus foot in bilateral spastic cerebral palsy - Horsch, Axel; Götze, Marco; Geisbüsch, Andreas; Beckmann, Nicholas A.; Tsitlakidis, Stefanos; Berrsche, Gregor; Klotz, Matthias C. M. (World journal of pediatrics, 2019)
Background: Equinus is a common deformity in children with bilateral spastic cerebral palsy (BSCP). While dynamic equinus usually is treated by conservative therapy, fixed contractures need surgical correction. To choose the appropriate surgical method, it is important to discriminate between isolated gastrocnemius shortening and combined gastrosoleus complex contracture.MethodsIn a retrospective study 938 patients with BSCP were studied. Patients underwent gait analysis and clinical examination. 248 patients (496 limbs) met the inclusion criteria. Data from motion analysis and clinical examination were used to calculate the prevalence and to further classify fixed equinus foot.ResultsThe prevalence of equinus was 83.3%. During clinical exam 246 (59.6%) limbs showed combined gastrosoleus complex contracture and 167 (40.4%) isolated gastrocnemius contracture. Max. DF at stance and mean DF at initial contact were significantly reduced in combined contracture, while max. ROM was increased (P < 0.05).Conclusions: Corroborating the results of previous studies, in this study there was a high prevalence of fixed equinus in patients with BSCP. The prevalence of equinus correlated with increasing age. As half of the patients with fixed equinus show a different involvement of gastrocnemius and soleus muscle, we recommend to apply Silfverskiöld’s test to discriminate between those two types to choose the appropriate surgical therapy.
Gesehen am 11.09.2019